1975
DOI: 10.1136/jnnp.38.8.776
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous neurilemmoma of the cervical spine causing paraparesis and treated by resection and grafting.

Abstract: SYNOPSIS A neurilemmoma presented as an expanding lesion of the bodies of C6 and C7 vertebrae and caused local neurological signs together with a spastic paraparesis. This tumour was treated by preliminary posterior fusion, followed by its complete removal via an anterior approach and stabilization by anterior spinal fusion. Other cases in the literature are reviewed and discussed.Solitary lesions affecting the vertebral bodies are uncommon and present problems in regard to both diagnosis and treatment. This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…During a follow-up period of 12 weeks her paraparesis had recovered almost completely. 10 Naidu et al reported an intraosseous schwannoma involving the bodies of the third and fourth cervical vertebrae causing tetraparesis. This patient was also diagnosed with skeletal fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…During a follow-up period of 12 weeks her paraparesis had recovered almost completely. 10 Naidu et al reported an intraosseous schwannoma involving the bodies of the third and fourth cervical vertebrae causing tetraparesis. This patient was also diagnosed with skeletal fluorosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although it can appear in any age, the usual age group is the third or fourth decade.There appears no predilection for sex. 2 They have been reported to arise in mandible 3 (most common), sacrum, 4 lumbar, 5 thoracic 6,7 and cervical vertebrae, 8,9 femur, 10 tibia, ® bula, 2 sternum, 11 calcaneum, 12 etc. The reason for the increased incidence in mandible is due to either the long intra-osseous course of the nerve or the increased predilection of schwanomas to the head and neck region, which has a large supply of sensory nerves.…”
Section: Discussionmentioning
confidence: 99%
“…The schwannoma of the cervical, thoracic and lumbar vertebrae usually present with pain 4,6,7 and/or neurological involvement. 5,8,9 The neurology differs with the level of the lesion.…”
Section: Intra-osseous Schwannoma Of Vertebraementioning
confidence: 99%
See 1 more Smart Citation
“…1 Of the seven published cases where the schwannoma arose from within the vertebra, only two have been reported in the cervical region. 3,4 We report a rare case of an intraosseous schwannoma involving the body of the fifth cervical (C5) vertebra that was diagnosed using magnetic resonance imaging following an incidental history of trauma.…”
Section: Introductionmentioning
confidence: 98%